Single, escalating dose pharmacokinetics, safety and food effects of a new oral androgen dimethandrolone undecanoate in man: a prototype oral male hormonal contraceptive. (2nd May 2014) - Surampudi, P.; Page, S. T.; Swerdloff, R. S.; Nya‐Ngatchou, J. J.; Liu, P. Y.; Amory, J. K.; Leung, A.; Hull, L.; Blithe, D. L.; Woo, J.; Bremner, W. J.; Wang, C.
Summary The novel androgen, dimethandrolone (DMA) has both androgenic and progestational activities, properties that may maximize gonadotropin suppression. We assessed the pharmacokinetics of dimethandrolone undecanoate (DMAU), an orally bioavailable, longer acting ester of DMA, for male contraceptive development. Our objective was to examine the safety and pharmacokinetics of single, escalating doses of DMAU (powder in capsule formulation) administered orally with or without food in healthy men. We conducted a randomized, double‐blind Phase 1 study. For each dose of DMAU (25–800 mg), 10 male volunteers received DMAU and two received placebo at two academic medical centres. DMAU was administered both fasting and after a high‐fat meal (200–800 mg doses). Serial serum samples were collected over 24 h following each dose. DMAU was well tolerated without significant effects on vital signs, safety laboratory tests or electrocardiograms. When administered while fasting, serum DMA (active compound) was detectable in only 4/10 participants after the 800 mg dose. When administered with a 50% fat meal, serum DMA was detectable in all participants given 200 mg DMAU and showed a dose‐incremental increase up to 800 mg, with peak levels 4–8 h after taking the dose. Serum gonadotropins and sex hormone concentrations were significantly suppressed 12 h after DMAU administration with food at doses above 200 mg. This first‐in‐man study demonstrated that a single, oral dose of DMAU up to 800 mg is safe. A high‐fat meal markedly improved DMAU/DMA pharmacokinetics.